The Effect of Working Capital Management on Profitability of Saudi Food and Beverages Corporations: An applied study (2015- 2019) - Hamoudah, Manal Mohammed; Algarni, Elaf Naser (Journal of Economic, Administrative and Legal Sciences, 2021)
The study examined the effect of working capital management (average inventory period, average collection period and average payment period), on the profitability of Saudi food and beverages corporations listed in Saudi exchange during five years from 2015 to 2019. In addition, company size, debt ratio and company age was used as control variables. The study used Return on Asset (ROA) and Return on Equity (ROE) as measures of firm profitability. To achieve the aim of the study, data were obtained from the annual financial reports published in the “Tadawul”, Saudia Arabia Stock Exchange, for a purposive sample of twelve (12) companies out of (203) Saudi corporations listed. Descriptive statistics and Multiple regression analysis were used to test the hypotheses of the study. The results indicated that ROA and ROE have been explained at 48%, and 55% respectively. Furthermore, the results found that there is statistically significant effect of average payment period on ROA. However, while the results found that there is statistically significant effect of all control variables on ROE, it did not find any significant effect of any the working capital management variables on ROE. Based on the results, we recommend that corporations need to pay attention to managing working capital in more efficient ways, especially through speed in collection and slow payment, which in turn lead to increased firm profitability.
Keywords: working capital management; rate of return on assets; rate of return on equity; Saudi food sector